Deleuze and design - Marenko, Betti; Brassett, Jamie (Edinburgh Edinburgh University Press, 2015)
"Drawing on a range of contributors, case studies and examples, this book examines ways in which we can think about design through Deleuze, and likewise how Deleuze's thought can be experimented upon and re-designed to produce new concepts. Discussions include materiality, creativity, objects, the future, innovation, the designed environment and the interaction between human non-human agents."--Back cover.
Poised and complex: the becoming each other of philosophy, design and innovation / Jamie Brassett -- Design in Guattari's ecosophy / Manola Antonioli -- Design machines and art machines / Anne Sauvagnargues -- Thinking hot: risk, prehension and sympathy in design / T. Hugh Crawford -- Digital materiality, morphogenesis and the intelligence of the technodigital object / Betti Marenko -- Re-designing the objectile / Derek Hales -- Design, assemblage and functionality / Vincent Beaubois -- Milieu and the creation of the illustrator: Chris Ware and Saul Steinberg / John O'Reilly -- Sustainable design activism: affirmative politics and fruitful future / Petra Hroch.
Includes bibliographical references and index.
Keywords: Deleuze, Gilles -- 1925-1995.; Design -- Philosophy